2021
DOI: 10.3390/pr9112040
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Chlorogenic Acid and Caffeine Content and Its Correlation with Coffee Bean Color under Different Roasting Degree and Sources of Coffee (Coffea arabica Typica)

Abstract: Coffee is one of the main economic crops in the world and is now widely grown throughout Taiwan. The process of roasting coffee begins with the heating and smooth expansion of raw beans, which leads to changes in appearance and color while affecting the flavor and taste of coffee. So far, most coffee manufacturers have used visual inspection or colorimeter methods to identify differences in coffee quality. Moreover, there is no literature discussing the correlation of roasted bean color with caffeine and chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
3
10
1
1
Order By: Relevance
“…No significant relationship between CQA content and colour characteristics was found in the present study, contrary to the results of Tsai and Jioe [ 20 ], who reported a strong correlation between CQA × L* and CQA × a*, respectively.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…No significant relationship between CQA content and colour characteristics was found in the present study, contrary to the results of Tsai and Jioe [ 20 ], who reported a strong correlation between CQA × L* and CQA × a*, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Irrespective of the above-mentioned differences, caffeine content reported by Król et al [ 24 ] was substantially lower in comparison with our data (12–13 mg g −1 , Table 1 ). A slightly higher caffeine content in dark-roasted as compared to light-roasted coffee was reported Tsai and Jioe [ 20 ].…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations